Integrated bioinformatic analysis and cell line experiments reveal the significant role of the novel immune checkpoint TIGIT in kidney renal clear cell carcinoma - Xia, Qi-Dong; Li, Bo; Sun, Jian-Xuan; Liu, Chen-Qian; Xu, Jin-Zhou; An, Ye; Xu, Meng-Yao; Zhang, Si-Han; Zhong, Xing-Yu; Zeng, Na; Ma, Si-Yang; He, Hao-Dong; et al. (Frontiers in Oncology, 2023)
Background: T cell immunoglobulin and ITIM domain (TIGIT) is a widely concerned immune checkpoint, which plays an essential role in immunosuppression and immune evasion. However, the role of TIGIT in normal organ tissues and renal clear cell carcinoma is unclear. Materials and methods: Data retrieved from the GTEX database and TCGA database was used to investigate the expression of TIGIT in normal whole-body tissues and abnormal pan-cancer, then the transcriptome atlas of patients with kidney renal clear cell carcinoma (KIRC) in the TCGA database were applied to distinguish the TIGIT related features. Furthermore, we constructed a gene-drug network to discover a potential drug targeting TIGIT and verified it by performing molecular docking. Finally, we conducted real-time polymerase chain reaction (PCR) and assays for Transwell migration and CCK-8 to explore the potential roles of TIGIT. Results: TIGIT was confirmed as an essential prognostic factor that was significantly higher expressed in KIRC tissues, and high expression of TIGIT is associated with poor OS, PFS, and DSS in KIRC. Also, high expression of TIGIT in KIRC was observed with several critical functions or pathways such as apoptosis, BCR signaling, TCR signaling et al. Moreover, the expression of TIGIT showed a strong positive correlation with infiltration of CD8+ T cells and Tregs and a positive correlation with the drug sensitivity of sunitinib simultaneously. Further Tide ips score analysis and submap analysis reveal that patients with high TIGIT expression significantly show a better response to anti-PD1 immunotherapy. Following this, we discovered Selumetinib and PD0325901 as potential drugs targeting TIGIT and verified the interaction between these two drugs and TIGIT protein by molecular docking. Finally, we verified the essential role of TIGIT in the proliferation and migration functions by using KIRC cell lines. Conclusions: TIGIT plays an essential role in tumorigenesis and progression in KIRC. High expression of TIGIT results in poor survival of KIRC and high drug sensitivity to sunitinib. Besides, Selumetinib and PD0325901 may be potential drugs targeting TIGIT, and combined therapy of anti-TIGIT and other treatments show great potential in treating KIRC.